2019
DOI: 10.3390/rs11242895
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Clock Performance Assessment of BeiDou-3 Basic System with the Noise Analysis of Orbit Determination and Time Synchronization

Abstract: The basic system of the BeiDou global navigation satellite system (BDS-3) with 18 satellites has been deployed since December 2018. As the primary frequency standard, BDS-3 satellites include two clock types with the passive hydrogen maser (PHM) and the rubidium atomic frequency standard (RAFS). Based on the final precise orbit and clock product from Xi’an Research Institute of Surveying and Mapping (XRS), the atomic clock performance of BDS-3 satellites is evaluated, including the frequency accuracy, frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Similarly, the C35-C37 clock accuracy is poor because of the small number of visible stations. The C25-C30, C34, and C35 satellites carry passive hydrogen atomic clocks, whereas the remaining satellites carry rubidium atomic clocks (Jia et al 2019). The clock STD difference between the two clock types is not evident.…”
Section: Pod Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, the C35-C37 clock accuracy is poor because of the small number of visible stations. The C25-C30, C34, and C35 satellites carry passive hydrogen atomic clocks, whereas the remaining satellites carry rubidium atomic clocks (Jia et al 2019). The clock STD difference between the two clock types is not evident.…”
Section: Pod Resultsmentioning
confidence: 93%
“…BDS-3 was announced to serve global users on December 27, 2018 (Yang et al 2019). Many scholars have evaluated the performance of BDS-3, including signal quality (Xu et al 2019;Zhang et al 2019;He et al 2020), realtime kinematics (Zhang et al 2019), precise point positioning (Zhang et al 2019), POD (Yan et al 2019;Zeng et al 2019a), and clock performance (Jia et al 2019). Li et al (2019) showed that there is no evident systematic bias between BDS-2 and BDS-3.…”
Section: Introductionmentioning
confidence: 99%
“…Since the end of 2018, the BDS-3 system has provided global service. A large number of scholars have studied the PNT service performance of BDS-3, and literature [4][5][6] has evaluated the signal quality of BDS-3. In the literature [7,8], the precise orbital determination of the BDS-3 satellite was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Literature [14] initially evaluated the positioning performance of single-frequency and dual-frequency BDS-3 RTK based on an ultra-short baseline, pointing out that the poor signal quality of B2a frequency of BDS- Since the end of 2018, the BDS-3 system has provided global service. A large number of scholars have studied the PNT service performance of BDS-3, and literature [4][5][6] has evaluated the signal quality of BDS-3. In the literature [7,8], the precise orbital determination of the BDS-3 satellite was studied.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of GNSS performance depends heavily on satellite clocks [ 3 , 4 ]. In recent years, there have been a number of publications containing clock stability analyses, but the majority of them cover only one or two GNSS systems [ 5 , 6 , 7 , 8 ]. Wang et al [ 9 ] analyzed BDS clocks with the use of Allan deviation, and similar research was conducted by Steigenberger [ 10 ], but using Galileo clocks.…”
Section: Introductionmentioning
confidence: 99%